Targeted delivery of siRNA using transferrin-coupled lipoplexes specifically sensitizes CD71 high expressing malignant cells to antibody-mediated complement attack - Cinci, Marc L.; Mamidi, Srinivas; Li, Wenhan; Fehring, Volker; Kirschfink, Michael (Targeted oncology, 2015)
The overexpression of membrane-bound complement regulatory proteins (mCRP; CD46, CD55, CD59) preventing opsonization and complement-dependent cytotoxicity (CDC) is considered a major barrier for successful antibody-based cancer immunotherapy. To avoid a potential deleterious effect of mCRP neutralization on normal tissue cells, complement regulation has to be selectively targeted to the malignant cells. In this study, anti-mCRP small interfering RNAs (siRNAs) were encapsulated in transferrin-coupled lipoplexes for the specific delivery to transferrin receptor CD71high expressing BT474, DU145, and SW480 as well as corresponding CD71-knockdown (CD71low) tumor cells. Targeted delivery with transferrin-siRNA-lipoplexes became possible by charge neutralization and resulted in efficient silencing of all three mCRPs up to 90 %, which is dependent on their CD71 expression. The mCRP knockdown led to a significant increase of CDC on CD71high tumor cells by 68 % in BT474, 58 % in DU145, and 40 % in SW480 cells but only slightly increased on CD71low cells. Downregulation of CD46 and CD55 significantly increased C3 opsonization only on CD71high tumor cells. Our results demonstrate for the first time that by specific delivery of anti-mCRP siRNA through transferrin receptor, complement regulation can be selectively neutralized, allowing specific antibody-mediated killing of tumor cells without affecting healthy bystander cells, which appears to be a suited strategy to improve antibody-based cancer immunotherapy.
Published: 15 November 2014
Gesehen am 14.10.2020